INTEGRATION OF DIGITAL TECHNOLOGY IN THE INHERITANCE DISTRIBUTION SYSTEM BASED ON FARAIDH LAW - Anggraini, Anggi Egi (AT-TAFAHUM: Journal of Islamic Law, 2025)
The development of digital technology offers new opportunities in resolving the challenges of inheritance distribution under faraidh, which has long been considered complex and prone to calculation errors. The main challenges include the diversity of heirs’ conditions, differences in interpretation among Islamic schools of thought, integration with national legal systems, and the protection of sensitive family data. On the other hand, the opportunities presented are efficiency, accuracy, transparency, and the educational function of helping society better understand inheritance distribution in accordance with Islamic law. This study aims to analyze how technology can assist in addressing inheritance distribution issues, particularly through the use of digital applications designed to automatically calculate heirs’ shares.The research employs a qualitative approach with a descriptive-analytical method. Data were obtained through literature studies on Islamic inheritance law, academic publications in information technology, and direct analysis of inheritance distribution applications. The research materials consist of digital inheritance calculators such as Hitung Waris and In Waris, which are used as samples to evaluate the effectiveness, strengths, and weaknesses of each application in practice. The analysis compares the applications’ calculation results with the requirements of faraidh law and examines the extent to which these applications meet societal needs. The findings are expected to provide a comprehensive overview of the contribution of technology in supporting the implementation of faraidh, while also highlighting the limitations that need improvement so that such applications can be more optimally utilized in the future.